New Challenges for the Eurozone Governance Joint Solutions for Common Threats? - Caetano, José; Vieira, Isabel; Caleiro, António (Springer International Publishing : Imprint: Springer, 2021)
XIX, 321 p. 59 illus., 39 illus. in color.